Anime tourists traveling to Japan: pilgrimage behaviors patterns and the formation of homologous emotions - Zheng, Rumin; Zhen, Shuo; Cai, Anning; Li, Sihan; Liu, Hongyu (Frontiers in Psychology, 2025)
IntroductionWith the rapid expansion of the tourism market and the increasing demand for personalized travel experiences, anime-themed cultural tourism has gained significant market attention due to its distinctive characteristics. This study focuses on the pilgrimage behavior and homologous emotion mechanism of Chinese anime tourists traveling to Japan.MethodsIt employs research methods including questionnaires, in-depth interviews, and participatory observation.ResultsThe findings reveal that anime tourists traveling to Japan exhibit strong youth-oriented demographics. Their high education levels and residence in economically developed cities provide a foundation for cultural consumption. In terms of behavioral characteristics, they display highly symbolic tourism consumption, productive social media engagement, and ritualized cultural identity expression. The formation of homologous emotions among anime tourists to Japan comprises five stages: symbolization of homologous emotions, ritualization of emotional expression, hierarchical construction of shared emotional identity, community-based communication and dynamic mechanisms of shared emotional influence. Based on these findings, recommendations include optimizing operational approaches in four key areas: cultural symbols, emotional value, industrial collaborative ecosystem, and digital dissemination-to promote sustainable anime tourism development.DiscussionThis study innovatively integrates emotional geography and symbolic consumption theory. It contributes valuable insights for understanding Generation Z's cultural consumption behavior and advancing the integration of culture and tourism.